2012
DOI: 10.1111/j.1468-2338.2012.00672.x
|View full text |Cite
|
Sign up to set email alerts
|

Involuntary part‐time workers in Britain: evidence from the labour force survey

Abstract: Part‐time employment is widely considered functional for the economy, with both benign and detrimental implications for employees. However, specific analyses of involuntary part‐time work in Britain are surprisingly absent from the flexibility debate, and workers in such positions remain largely under‐researched. This article explores involuntary part‐time employment in relation to socio‐economic circumstances. We analyse Labour Force Survey data, using logistic regression modelling to identify the segments of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 46 publications
1
21
0
3
Order By: Relevance
“…This is evidenced in the pay gap for part-time female workers (in comparison with male full-time workers) in the UK, which stands at 38.8% (Perfect, 2011). Women in the UK who work part-time mostly do so in order to combine work with childcare commitments, whereas men in the UK are proportionally much more likely to report that they work part-time because they are unable to find a full-time job (IPPR, 2010;Cam, 2011). Indeed, male part-time workers earn less on average than female part-time workers in the UK (ECHRC, 2010), suggesting that this is unlikely to be an outcome of choice for men with other options.…”
Section: Hypothesis 1a -That Ethnic Minority Men Are Significantly Momentioning
confidence: 99%
“…This is evidenced in the pay gap for part-time female workers (in comparison with male full-time workers) in the UK, which stands at 38.8% (Perfect, 2011). Women in the UK who work part-time mostly do so in order to combine work with childcare commitments, whereas men in the UK are proportionally much more likely to report that they work part-time because they are unable to find a full-time job (IPPR, 2010;Cam, 2011). Indeed, male part-time workers earn less on average than female part-time workers in the UK (ECHRC, 2010), suggesting that this is unlikely to be an outcome of choice for men with other options.…”
Section: Hypothesis 1a -That Ethnic Minority Men Are Significantly Momentioning
confidence: 99%
“…It was also reported that women part-time employees had more job satisfaction than men due to a better work-life balance (Bonney, 2005). However, the recent evidence points to a higher level of involuntariness among women for part-time jobs than men (Bell & Blanchflower, 2011;Cam, 2012).…”
Section: Demographic Factorsmentioning
confidence: 90%
“…Roughly 30% of British employees work in part-time jobs (LFS, 2012), compared to less than 18% average in the G7 countries (OECD, 2010). Since the beginning of the recession in Britain, there has been an increase in involuntary part-time jobs -as defined by being unable to obtain full-time contracts (Cam, 2012). Research evidence from Denmark (Lind & Rasmussen, 2008) and Norway (Kjeldstad & Nymoen, 2012) also suggests that part-time jobs imply higher levels of underemployment.…”
Section: Journal Of Social Science Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The increase in involuntary part-time work during the downturn has been mainly in low-paid jobs. Part-time unemployment is more likely to be involuntary for people with lower educational and occupational levels (Cam, 2012). Even though involuntary part-time work has increased for both genders, the rise is particularly sharp for men.…”
Section: Working Hours Have Adjusted To Weak Activitymentioning
confidence: 99%